Medication–Sedation Interactions In Dental Procedures: A Multidisciplinary Approach Involving Dentists, Anesthetists, And Pharmacists (The Review of Diabetic Studies, 2024)
Sedation is widely used in dental practice to facilitate patient comfort, anxiety control, and procedural success. However, the expanding use of sedative agents in outpatient dental settings coincides with increasing polypharmacy among pediatric, adult, and geriatric patients. Medication–sedation interactions represent a critical yet under-recognized source of preventable adverse events, including respiratory depression, cardiovascular instability, delayed recovery, and paradoxical reactions. This narrative review examines pharmacodynamic and pharmacokinetic interactions between commonly prescribed medications and dental sedation agents, emphasizing the coordinated roles of dentists, anesthetists, and pharmacists. Through an interprofessional framework, the review highlights risk stratification, pre-procedural medication reconciliation, sedation planning, intra-procedural monitoring, and post-procedural safety. Strengthening multidisciplinary collaboration is essential for optimizing sedation safety and reducing preventable harm in contemporary dental practice.